Analisis Yuridis Terhadap Penegakan dan Pengaturan Hukum Kejahatan Dunia Maya (Cyebercrime) di Indonesia - Elok Harry Ari Dhani Putri; Ramdhan Kasim; Leni Dwi Nurmala (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The aim of this research is to find out and analyze cybercrime law enforcement in Indonesia. The implementation of this research is normative research. Data analysis is an activity in research in the form of conducting studies or reviewing the results of data processing which is assisted by previously obtained theories. Cyber crime law enforcement in Indonesia can be carried out penal and non-penal. In general, seen from criminal policy (crime prevention policy), criminal law is not a strategic policy tool to prevent and eliminate causal factors or conditions that give rise to crime. We can see the positive criminal law provisions that are criminalized regarding cyber crime in Law Number 19 of 2016, amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. Meanwhile, non-penal measures are carried out through social methods or approaches such as information, appeals, educational channels, coaching, and also related matters of preventing cyber crime. In realizing law enforcement, law enforcement officers need an active role, namely by being equipped with special skills in handling cyber crime.